2019
DOI: 10.3390/app9204271
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes Translocation through a Lipid Membrane and Transporting Small Hydrophobic and Hydrophilic Molecules

Abstract: Carbon nanotubes (CNTs) are extensively adopted in the applications of biotechnology and biomedicine. Their interactions with cell membranes are of great importance for understanding the toxicity of CNTs and the application of drug delivery. In this paper, we use atomic molecular dynamics simulations to study the permeation and orientation of pristine and functionalized CNTs in a lipid bilayer. Pristine CNT (PCNT) can readily permeate into the membrane and reside in the hydrophobic region without specific orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…75 It has been shown that hydroxyl-modified CNTs tend to be vertical to the bilayer center when the length of the CNT is shorter than the bilayer thickness. 81 However, by varying the grafting density of PSCOOH at the end of CNTs, we didn't observe a hindrance effect. But wider tilt angle distributions were observed mostly at ~10°-20° range (cf.…”
Section: Interaction Of Cnt Models With Lipid Bilayersmentioning
confidence: 73%
See 1 more Smart Citation
“…75 It has been shown that hydroxyl-modified CNTs tend to be vertical to the bilayer center when the length of the CNT is shorter than the bilayer thickness. 81 However, by varying the grafting density of PSCOOH at the end of CNTs, we didn't observe a hindrance effect. But wider tilt angle distributions were observed mostly at ~10°-20° range (cf.…”
Section: Interaction Of Cnt Models With Lipid Bilayersmentioning
confidence: 73%
“…CNTs spontaneously diffuse into the membranes as reported elsewhere. 29,30,81 In homogeneous bilayers which consist of a single lipid component, the APL can be calculated simply by dividing the average box area into half the lipid number. However, this method is not suitable for heterogeneous bilayers containing various types of lipids of different sizes, such as CHOL.…”
Section: Interaction Of Cnt Models With Lipid Bilayersmentioning
confidence: 99%
“…For modeling, the structure of a closed single-walled carbon nanotube was chosen, which is 348 carbon atoms 12 C, located in space so that, while remaining a surface crystal, this structure had a significant space inside, isolated by the surface of the tube from the external environment. Three model CH 4 methane molecules were placed in this space, located on the symmetry axis of the nanotube as follows.…”
Section: Methodsmentioning
confidence: 99%
“…At high CNT densities, lipid-mediated interactions facilitate CNT diffusion and drive CNTs to assemble into clusters of 2D hexagonal arrays spaced apart by the annular lipid shells [440]. Other simulations found that while CNTs had virtually no effect on the structural properties of the membrane they cause slight ordering in neighboring lipid tails [407].…”
Section: Nanoparticlesmentioning
confidence: 99%